Efektifitas Tandan Kosong Kelapa Sawit (Elais Guineensis Jacq) Dalam Menurunkan Kadar COD Limbah Cair Kain Jumputan - Zairinayati Zairinayati; Khoriatul Khosamtun (Indobiosains, 2022)
The textile industry in South Sumatra is progressing and has a positive impact on people's lives, the activities of this industry have the potential to generate liquid waste. This will disturb the quality of water bodies, especially the presence of oxygen. The adsorption process was chosen as a waste treatment method because it is relatively simple and can use natural material adsorbents from the waste of unused biomass.This research aims toto know the effectiveness of palm empty bunches activated carbon (Elais guineensis Jacq) in adsorbing COD in the wastewater of jumputan fabric in Palembang. with variations in activated carbon of oil palm empty bunches and wood charcoal, namely 20 grams, 40 grams and 60 grams with a contact time of 45 minutes for each test. The test results showed that the COD value before treatment was 40 mg / l and after treatment using oil palm empty sign activated carbon was 109 mg / l on average and wood charcoal activated carbon averaged 166.67 mg / l. Anova test results on 2 types of activated carbon showed no difference in decreasing COD levels in the waste water of Palembang jumputan.